HAPPENING ART DALAM AKSI DEMONSTRASI MASSA DI YOGYAKARTA - Trie Wahyuni (FBS UNY, 2007)
This study is aimed at identifying the forms and the purpose of happening art performance in mass demonstration frequently taking place nowadays. The subject of the study is the primary resources, namely the mass demonstration agents consisting of the activators, the performers and the supporters, as well as the viewers or the society in Yogyakarta watching the performance in the demonstration. The data were collected through observation, documentation, literature and interviews. The study shows that the form of the happening art performance consists of some elements like: 1) duration, 2) performers, 3) make-up, 4) costume, 5) stage, 6) property, 7) dance movements, and 9) verbal expressions. Meanwhile the purpose of performing a happening art is to make the demonstration easy to be understood by the society. Key Words: happening art, mass demonstration